Association Between Muscle Mass Determined by D3‐Creatine Dilution and Incident Fractures in a Prospective Cohort Study of Older Men. (6th March 2022) - Cawthon, Peggy M.; Peters, Katherine E.; Cummings, Steven R.; Orwoll, Eric S.; Hoffman, Andrew R.; Ensrud, Kristine E.; Cauley, Jane A.; Evans, William J.; ,
ABSTRACT: The relation between a novel measure of total skeletal muscle mass (assessed by D3 ‐creatine dilution [D3 Cr]) and incident fracture is unknown. In 1363 men (mean age 84.2 years), we determined D3 Cr muscle mass; Fracture Risk Assessment Tool (FRAX) 10‐year probability of hip and major osteoporotic (hip, humerus, vertebral, forearm) fracture; and femoral neck bone mineral density (BMD) (by dual‐energy X‐ray absorptiometry [DXA]). Incident fractures were centrally adjudicated by review of radiology reports over 4.6 years. Correlations adjusted for weight and height were calculated between femoral neck BMD and D3 Cr muscle mass. Across quartiles of D3 Cr muscle mass/weight, proportional hazards models calculated hazard ratios (HRs) for any ( n = 180); nonspine ( n = 153); major osteoporotic fracture ( n = 85); and hip fracture ( n = 40) after adjustment for age, femoral neck BMD, recurrent fall history, and FRAX probability. Models were then adjusted to evaluate the mediating influence of physical performance (walking speed, chair stands, and grip strength). D3 Cr muscle mass was weakly correlated with femoral BMD ( r = 0.10, p < 0.001). Compared to men in the highest quartile, those in the lowest quartile of D3 Cr muscle mass/weight had an increased risk of any clinical fracture (HR 1.8; 95% confidence interval [CI], 1.1–2.8); nonspine fracture (HR 1.8; 95% CI, 1.1–3.0), major osteoporotic fracture (HR 2.3; 95% CI, 1.2–4.6), and hip fracture (HR 5.9; 95% CI, 1.6–21.1). Results were attenuated after adjustment for physical performance, but associations remained borderline significant for hip and major osteoporotic fractures ( p ≥ 0.05 to 0.10). Low D3 Cr muscle mass/weight is associated with a markedly high risk of hip and potentially other fractures in older men; this association is partially mediated by physical performance. © 2022 American Society for Bone and Mineral Research (ASBMR).